An ultra-microporous organic polymer for high performance carbon dioxide capture and separation1. Issue 69 (7th September 2015) - Sekizkardes, Ali Kemal; Culp, Jeffrey T.; Islamoglu, Timur; Marti, Anne; Hopkinson, David; Myers, Christina; El-Kaderi, Hani M.; Nulwala, Hunaid B.
<x xml:space="preserve">Abstract</x> Rationally designed porous organic polymer for CO2 capture and separation.